The Principle Of Good Faith In Collective Labor Agreements Between Employers And Labor Unions In Review Of Contract Law - Safrida, Safrida (International Journal of Educational Research & Social Sciences, 2024)
The principle of good faith is an important principle in contract law and is accepted in variouslegal systems, but until now the doctrine of good faith is still controversial Good faith is knownby 2 (two) phases, namely the pre-contract phase and the contract execution phase. The precontract phase is called subjective good faith, which means that good faith is more directedtowards honesty, while good faith in the contract implementation phase is called objective goodfaith, which means that good faith is interpreted as appropriateness and decency or justice. Awork agreement is an agreement between workers/laborers and employers or employers thatcontains working conditions, rights and obligations for the parties. The definition of workingconditions is the rights and obligations of employers and workers that have not been regulatedin laws and regulations. Work agreements made must not conflict with existing laboragreements or Collective Labor Agreements (KKB)/Collective Labor Agreements (PKB). Thisresearch uses normative legal research sourced from secondary data related to the researchtopic, secondary data that has been regularly arranged and then analyzed qualitatively. Fromthe research conducted, it was found that the position of the principle of good faith is veryimportant not only at the stage of making (signing) and post-making (implementation) of thecontract, but also at the pre-making (drafting) ) stage of the contract because in the practice ofcontract law the judge does use his authority to interfere with the contents of the contract. Thelegal consequences of a collective bargaining agreement that does not contain the principle ofgood faith are that if the subjective requirements concerning the subject of the CBA areincomplete, or in other words the requirements that must be met are not appropriate for thosewho wish to make a CBA, then the CBA that has been made can be requested for cancellation bythe trade union/labor union. If the cancellation is not requested by both parties concerned, thenthe PKB remains valid for the parties. The first legal effort made by PT United Rope with thelabor union is by way of deliberation to reach consensus first, although in dispute resolution ifthere is no good faith in the collective labor agreement is through 2 (two) systems, namely first,non -litigation / outside the industrial relations court, namely bipartite settlement, mediation,conciliation and arbitration, while the second settlement is litigation.